Pengaruh Keamanan, Kepercayaan dan Gaya Hidup Terhadap Loyalitas Pengguna e-Wallet di Kota Banjarmasin - Salsadila Zahra Ananda; Fadma Yulianti; Ibrahim Daud; Lydia Goenadhi (LPPM Universitas KH A. Wahab Hasbullah, 2026)
This research focuses on how security, trust, and lifestyle relate to the loyalty of DANA e-wallet users in Banjarmasin City. A quantitative approach was applied by distributing a survey of 68 DANA users selected based on domicile, age, and usage intensity criteria. Responses were collected using questionnaires and then tested through a multiple linear regression model with SPSS version 25. The analysis found that security has not become a significant factor in maintaining user loyalty. In contrast, trust and lifestyle have significant effects. Overall, the simultaneous test shows that the three variables still contribute significantly to user loyalty. These results indicate that loyalty is not sufficiently explained by security aspects alone, but also by users’ confidence in the service and the suitability of application features with daily activity patterns. These findings place trust and service relevance as important elements in maintaining DANA user loyalty. However, these findings should be read by considering the characteristics of the respondents who were dominated by young users, so generalization to all DANA users in Banjarmasin City needs to be carried out carefully.